2020
DOI: 10.1029/2019gl086053
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Estimated Electron Lifetimes in the Earth's Radiation Belts: Van Allen Probe Observations

Abstract: We use measurements from NASA's Van Allen Probes to calculate the decay time constants for electrons over a wide range of energies (30 keV to 4 MeV) and L values ( L = 1.3–6.0) in the Earth's radiation belts. Using an automated routine to identify flux decay events, we construct a large database of lifetimes for near‐equatorially mirroring electrons over a 5‐year interval. We provide the first accurate estimates of the long decay timescales in the inner zone ( ∼100 days), which are highly resolved in energy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
69
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(93 citation statements)
references
References 25 publications
14
69
1
Order By: Relevance
“…The lifetimes are calculated using Equation 5 of Ni et al (2013). These lifetime values are comparable to previous results calculated in theory (e.g., Abel & Thorne, 1998; Albert et al, 2020; Claudepierre et al, 2020b; Mourenas et al, 2017; Ross et al, 2019) and inferred from observations (Claudepierre et al, 2020a; Ripoll et al, 2014). The lifetime of the electron flux due to collision + hiss + LGW is much shorter than that due to collision + hiss because the deep minimum of < D αα > at PA = [65°, 85°] from hiss waves is significantly filled by LGW waves (Figure 2e).…”
Section: Comparisons Between Simulations and Observationssupporting
confidence: 91%
See 1 more Smart Citation
“…The lifetimes are calculated using Equation 5 of Ni et al (2013). These lifetime values are comparable to previous results calculated in theory (e.g., Abel & Thorne, 1998; Albert et al, 2020; Claudepierre et al, 2020b; Mourenas et al, 2017; Ross et al, 2019) and inferred from observations (Claudepierre et al, 2020a; Ripoll et al, 2014). The lifetime of the electron flux due to collision + hiss + LGW is much shorter than that due to collision + hiss because the deep minimum of < D αα > at PA = [65°, 85°] from hiss waves is significantly filled by LGW waves (Figure 2e).…”
Section: Comparisons Between Simulations and Observationssupporting
confidence: 91%
“…This model contains the azimuthal drift effect, PA diffusion induced by various plasma waves, and a CRAND source. Recently, the scattering effects of different waves on electrons in the slot region have been a topic of active research (Albert et al, 2016(Albert et al, , 2020Claudepierre et al, 2020aClaudepierre et al, , 2020bRoss et al, 2019). The wave models in these studies are mostly empirical, and their calculated results showed limited quantitative comparisons with specific satellite measurements during extend quiet times.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been devoted to calculate electron lifetimes throughout the radiation belts (Albert & Shprits, 2009; Baker et al., 2013; Claudepierre et al., 2020; Fennell et al., 2013; Meredith et al., 2002). Precise calculations of electron lifetimes are crucial for accurately modeling and forecasting the global dynamics of the outer radiation belt and for providing a comprehensive description of electron flux variations over a wide energy range.…”
Section: Discussionmentioning
confidence: 99%
“…Relativistic electron fluxes can be increased by several orders of magnitude (Baker et al, 1994; Reeves et al, 2003) on the timescale of hours to days and can pose a risk to satellite instrumentation (Wrenn et al, 2002). These fluxes then decay on timescales of 5–10 days (Claudepierre et al, 2020; Meredith et al, 2006), and it is believed that their removal is strongly influenced by pitch angle diffusion by electromagnetic ion cyclotron (EMIC) waves (Albert, 2003; Horne & Thorne, 1998). Coincident observations of EMIC waves and relativistic electron precipitation support the idea that EMIC waves are influential at scattering MeV electrons (Miyoshi et al, 2008; Rodger et al, 2008; Usanova et al, 2014; Yuan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%